Solve for k
k=-8+6\sqrt{3}i\approx -8+10.392304845i
k=-6\sqrt{3}i-8\approx -8-10.392304845i
Share
Copied to clipboard
16k^{2}-32k+16-18k^{2}=360
Subtract 18k^{2} from both sides.
-2k^{2}-32k+16=360
Combine 16k^{2} and -18k^{2} to get -2k^{2}.
-2k^{2}-32k+16-360=0
Subtract 360 from both sides.
-2k^{2}-32k-344=0
Subtract 360 from 16 to get -344.
k=\frac{-\left(-32\right)±\sqrt{\left(-32\right)^{2}-4\left(-2\right)\left(-344\right)}}{2\left(-2\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -2 for a, -32 for b, and -344 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
k=\frac{-\left(-32\right)±\sqrt{1024-4\left(-2\right)\left(-344\right)}}{2\left(-2\right)}
Square -32.
k=\frac{-\left(-32\right)±\sqrt{1024+8\left(-344\right)}}{2\left(-2\right)}
Multiply -4 times -2.
k=\frac{-\left(-32\right)±\sqrt{1024-2752}}{2\left(-2\right)}
Multiply 8 times -344.
k=\frac{-\left(-32\right)±\sqrt{-1728}}{2\left(-2\right)}
Add 1024 to -2752.
k=\frac{-\left(-32\right)±24\sqrt{3}i}{2\left(-2\right)}
Take the square root of -1728.
k=\frac{32±24\sqrt{3}i}{2\left(-2\right)}
The opposite of -32 is 32.
k=\frac{32±24\sqrt{3}i}{-4}
Multiply 2 times -2.
k=\frac{32+24\sqrt{3}i}{-4}
Now solve the equation k=\frac{32±24\sqrt{3}i}{-4} when ± is plus. Add 32 to 24i\sqrt{3}.
k=-6\sqrt{3}i-8
Divide 32+24i\sqrt{3} by -4.
k=\frac{-24\sqrt{3}i+32}{-4}
Now solve the equation k=\frac{32±24\sqrt{3}i}{-4} when ± is minus. Subtract 24i\sqrt{3} from 32.
k=-8+6\sqrt{3}i
Divide 32-24i\sqrt{3} by -4.
k=-6\sqrt{3}i-8 k=-8+6\sqrt{3}i
The equation is now solved.
16k^{2}-32k+16-18k^{2}=360
Subtract 18k^{2} from both sides.
-2k^{2}-32k+16=360
Combine 16k^{2} and -18k^{2} to get -2k^{2}.
-2k^{2}-32k=360-16
Subtract 16 from both sides.
-2k^{2}-32k=344
Subtract 16 from 360 to get 344.
\frac{-2k^{2}-32k}{-2}=\frac{344}{-2}
Divide both sides by -2.
k^{2}+\left(-\frac{32}{-2}\right)k=\frac{344}{-2}
Dividing by -2 undoes the multiplication by -2.
k^{2}+16k=\frac{344}{-2}
Divide -32 by -2.
k^{2}+16k=-172
Divide 344 by -2.
k^{2}+16k+8^{2}=-172+8^{2}
Divide 16, the coefficient of the x term, by 2 to get 8. Then add the square of 8 to both sides of the equation. This step makes the left hand side of the equation a perfect square.
k^{2}+16k+64=-172+64
Square 8.
k^{2}+16k+64=-108
Add -172 to 64.
\left(k+8\right)^{2}=-108
Factor k^{2}+16k+64. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(k+8\right)^{2}}=\sqrt{-108}
Take the square root of both sides of the equation.
k+8=6\sqrt{3}i k+8=-6\sqrt{3}i
Simplify.
k=-8+6\sqrt{3}i k=-6\sqrt{3}i-8
Subtract 8 from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}